2012
DOI: 10.4162/nrp.2012.6.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns based on carbohydrate nutrition are associated with the risk for diabetes and dyslipidemia

Abstract: Several studies have been conducted on dietary patterns based on carbohydrate nutrition in Asian populations. We examined the cross-sectional associations in dietary patterns based on carbohydrate nutrition, including the glycemic index (GI) with dyslipidemia and diabetes among the Korean adult population. We analyzed 9,725 subjects (3,795 men and 5,930 women, ≥ 20 years) from the Fourth Korea National Health and Nutrition Examination Survey. Dietary information was collected using single 24-hour recall. Reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(33 citation statements)
references
References 39 publications
3
28
0
2
Order By: Relevance
“…However, several other lifestyle factors have been shown to be related to lipid levels in adults, including dietary habits and the intake of certain foods. [26][27][28][29]34]. …”
Section: Physical Activitymentioning
confidence: 99%
“…However, several other lifestyle factors have been shown to be related to lipid levels in adults, including dietary habits and the intake of certain foods. [26][27][28][29]34]. …”
Section: Physical Activitymentioning
confidence: 99%
“…Contudo, Takahashi et al 29 constataram que a ingestão de frutas e vegetais é considerado fator de proteção para hipergliceridemia e que o excesso de gordura central e periférica é um importante marcador de dislipedimia. Song e colaboradores 30 ressaltam ainda que o consumo em excesso de carboidratos esteja diretamente ligado ao risco de desenvolver dislipidemia.…”
Section: Discussionunclassified
“…The studies on Asian population have also shown positive effects of dietary patterns characterized by high consumption of vegetables, fruits, whole grains and fish on the reduction risk of having high cholesterol or/and triglyceride [27][28][29][30]39]. On the other hands, the dietary patterns rich in sugar, sweets and refined grains increase the risk of having low HDL-c and/or high triglyceride [27,28,30,39,40]. According to our knowledge there is no study which investigated the association between lipid abnormalities and dietary patterns singly in diabetic patients.…”
Section: Introductionmentioning
confidence: 99%